Optimasi Indikator Linear Weighted Moving Average Menggunakan Teknik Martingale sebagai Metode Peningkatan Profit Trading - Baraja, Abdillah (INTEGER: Journal of Information Technology, 2021)
Forex Trading is familiar to ordinary people as a way of investing, many of investor buying and selling transactions of foreign exchange or stocks using the MetaTrader software as a direct bridge to the forex or stock market. One method to find out the trends in the capital market is to use pre-installed indicator or directly listen to economic news. Linear Weighted Moving Average as one of the favorite indicators in forex or stock traders as it for individuals or bank managers, it is the most widely used for analyzing the direction of the capital market. The Linear Weighted Moving Average is not a holy grail whose are one hundred percent correct, it is because the volatile of forex and stock changes. The auto trading script (expert advisor) provided by Metatrader still has weaknesses due to incorrect predictions and resulting in reducing balance from investors' capital. The expectations from this research that martingale technique to optimize Linear Weighted Moving Average indicator in every forex transaction to increase profits in forex or stock trading.Keywords: Forex Trading, Martingale, Linear Weighted Moving Average